DESKRIPSI PENYELESAIAN SOAL CERITA MATERI PECAHAN DITINJAU DARI TAHAPAN O’NEIL SMP KRISTEN KANAAN KUBU RAYA - Ainur Rahmi; Agung Hartoyo; Ahmad Yani T (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2017)
Abstract This research aims to determine the steps of problem solving in fraction material in the form of story questions which the students did with high, moderate and low level of capability based on O’Neil steps. Method of the research in qualitative descriptive in the form of case study. The participant of the research is 24 students of 7th grade in SMP Kristen Kanaan Kubu Raya 2016/2017. The result of test analysis shows that the steps of problem solving which the students did very in the use of problem solving steps in every question. Besides that, not all of the student from every level applied this O’Neil steps. However, the steps of problem solving by the hight group students appeared to be better than the moderate and low level students. Likewise, the process of problem solving by the moderate level students appeared to be better than the low level students.Keywords: Problem Solving Capability, O’Neil Steps